SENI, ILMU, DAN AGAMA Memotret Tiga Dunia Kuntowijoyo (1943-2005) Dengan Kacamata Integral(isme) - Riyanto, Waryani Fajar (JPP (Jurnal Politik Profetik), 2013)
This article is aimed to present Kunto in three different angles: religion, arts and science. Religion here means the thought of Kunto in dealing with Islamic religious thought (objectivity). Arts may mean Kunto’s thought on literature (prophetic literature) and science here may be defined as Kunto’s thought on social and cultural sciences, particularly on historical sciences (Islamic historiography in Indonesia). Based on this, the writer may call ‘three worlds’ of Kunto as a religious man, an artist and a scientist at the same time (historian and culturalist). These three intermingled words are what the writer refers as intellectual ascetism, which should, not to say must, be possessed by all scientists of any disciplines.